Velocidade de onda ultrassônica longitudinal e transversal em concretos estruturais de variadas resistências submetidos à compressão simples e à tração por compressão diametral. - Araújo, Andreza Vera Pyrrho de (2015)
The work discusses the about the behavior of longitudinal and transverse ultrasonic waves om concrete of several compressive strength loaded in compression on axial and diametral direction. 112 cylindrical test specimens, built from concretes with strength levels within the range prescribed by Brazilian code NBR 6118/2014, were made. Compressive strength, splitting and modulus of elasticity were performed in all specimens withe longitudinal and transverse ultrasonic waves were also induced. Seven mixing ratios were made being fine of then from concrete and two from mortar materials. For each mixing ratio, 16 test specimens were made totaling 112 cylindrical specimens. Results obtained show that there are changes longitudinal e transverse ultrasonic pulse velocity in concrete with the increase of the stress level. During the performed test it was also observed that the variations on ultrasonic pulse velocity often occurred near the maximum level of stress when elastic properties of concrete begin to deteriorate.